DEVELOPMENT OF DIGITAL SALES CHANNELS OF BANKING PRODUCTS AND SERVICES - Dmitro Mangushev; Volodymyr Shvets; Yevheniia Artomenko (Соціальна економіка)
The article examines the main stages of the development of digital channels for the sale of banking products and services. In particular, such stages as traditional banking, development of digital channels, multi-channel service and dominance of digital sales channels are highlighted. At the stage of traditional banking, the predominant sales channel for banking products and services are physical bank branches. At the second stage, banks begin to master electronic sales channels, their share in sales increases. At the third stage, banks begin to actively apply and build a balanced model of traditional and alternative sales channels, along with Internet banking, mobile banking is becoming widespread. In the fourth stage, digital sales channels prevail over traditional ones, and only complex banking products are sold in branches. Neobanks are characterized as a business model for banks at the stage of dominance of digital sales channels. The trend is for neobanks to expand into new markets, such as SME lending and investment services, as well as partnerships with traditional financial institutions. Alternative approaches to structuring the stages of development of digital sales channels are considered. The main characteristics of Internet and mobile banking as the main digital sales channels are summarized. It found that banks should continue to improve the value proposition of digital sales channels by focusing on developing the online banking experience, rather than just looking at phasing it out in favor of mobile banking. One of the most common trends in mobile banking is the extraordinary functionality of the application. Mobile banking should not be an additional alternative application with a minimum of functions that complement Internet banking. Rather, it is a full-fledged access channel to all banking products.